Pethia longicauda, a new species of barb (Teleostei: Cyprinidae) from the northern Western Ghats, India - Katwate, Unmesh; Paingankar, Mandar S.; Raghavan, Rajeev; Dahanukar, Neelesh (Zootaxa, 2014)
Pethia longicauda, a new cyprinid fish, is described from Hiranyakeshi River, Krishna drainage, Maharashtra, India. It can be distinguished from congeners based on a combination of characters including: a long caudal peduncle, incomplete lateral line, absence of barbels, upper lip thick and fleshy, distinct lateral fold on snout, 22–24 scales in lateral series, 5–6 lateral-line pored scales, nine predorsal scales, 9–10 prepelvic scales, 15–17 preanal scales, ½3/1/3½ transverse scales, 11–15 pairs of serrae on the distal half of the last unbranched dorsal-fin ray, 11–13 branched pectoral fin rays, 4+26 total vertebrae, 4+5 predorsal vertebrae, 4+13 abdominal and 13 caudal vertebrae, body iridescent silver in color with a black humeral spot, two black blotches on caudal peduncle and dorsal fin usually without any color bands or blotches but in breeding males with two rows of minute, indistinct black spots.